Plasma total and donor-derived cell-free DNA predict survival in kidney transplant recipients - Graver, Alison S.; Power, David A.; Whitlam, John B. (Frontiers in Transplantation, 2025)
IntroductionStudies evaluating cell-free DNA (cfDNA) in kidney allograft dysfunction have primarily focused on detection of rejection by donor-derived cfDNA (ddcfDNA). The utility of ddcfDNA as a marker of longer-term outcomes has not been examined.MethodsThis study investigated the prognostic value of plasma total cfDNA, fractional ddcfDNA and absolute ddcfDNA, quantified in 49 adult kidney transplant recipients (KTRs) at the time of indication allograft biopsy between 2014 and 2017. Primary outcomes were death, death-censored graft loss (DCGL), and all graft loss (AGL).ResultsDuring a median follow-up of 6.3 years, 7 patients died, 7 experienced DCGL, and 14 had AGL. Death was predicted by high total cfDNA [>4,034 copies/ml, hazard ratio (HR) 5.94, 95% CI 1.40–25.13, P = 0.008] and low fractional ddcfDNA (<0.67%, HR 10.85, 95% CI 1.32–1,408.19, P = 0.03), and DCGL was predicted by high fractional ddcfDNA (>0.72%, HR 4.93, 95% CI 1.12–21.72, P = 0.04), on univariate analysis. AGL was predicted by high total cfDNA (>4,034 copies/ml, HR 642, 95% CI 1.15–3.56 × 105, P = 0.045) on multivariate analysis. Absolute ddcfDNA was not associated with survival outcomes.DiscussionThis study demonstrates potential prognostic utility of total cfDNA and fractional ddcfDNA in KTRs with allograft dysfunction. Incorporation of these biomarkers could enhance personalised care, beyond non-invasive detection of rejection.